Professional Ethics of Nurses, Midwives in Work Motivation and Transformational Leadership Style Towards the Performance of Nurses and Midwives at Budiasih Mother and Child Hospital - Prabowo, Bahtiar (Alliance of Health Activists (AloHA), 2024)
In line with the era of reform that develops in society with its various demands, it needs to be addressed positively by multiple parties. Nurses and midwives are the central factors that drive organizational dynamics, so the facilities and infrastructure owned by the organization will be dynamic if they are appropriately managed by nurses and midwives who have high quality. Nurses and midwives are essential assets that must be maintained by companies mainly engaged in service services that rely on the level of performance of nurses and midwives in the company. The method used in this study was the cross-sectional approach. The total population was 167 employees. The author used his sample of respondents, as many as 62.5/62 nurse and midwife respondents. Independent variables were work motivation and transformtional leadrship style, while dependent was employee performance. Data were collected using questionnaires, then analyzed using multiple linear regression test. Based on the results, the equation was Y = 9.883 + 0.346 X1 + 0.323 X2, when X1 = work motivation, X2 = transformational leadership style, Y = employee performance, a = constant, b = coefficient. Based on the research results, it can be concluded that work motivation and transformational leadership style are determinants of the performance of nurses and midwives at Budiasih Mother and Child Hospital, Serang, Indonesia. Keywords: professional ethics; motivation; transformational; performance; nurses; midwives